PETER ACCORDING TO PAUL. PAUL AND PETER IN PAUL’S LETTERS AND IN THE BOOK OF ACTS AND THE PROBLEM OF PLURALITY IN THE CHURCH - Niebuhr, Karl-Wilhelm (Sacra scripta, 2023)
The apostles Peter and Paul are prominent as the two leading figures in early Christianity as well as in the history of the church through the centuries. They also function as focal for Christian confessions in particular ways until today. In historical approaches to the origins of Christianity following the direction of the "Tübingen School" (F. C. Baur) both Peter and Paul were considered two opposite powers that pushed ahead the historical development. In contrast, the following essay argues that, read in a canonical perspective as well as in a historical perspective that is critical against its own prejudices, the two key apostles can be valued much more in agreement to each other, notwithstanding their differences with regard to their particular function and mission in the beginnings of the early Jesus-movement. Therefore, Peter and Paul can be regarded as a model for ecumenical encounter and search for communion between the churches today.